Higher order photoprotection mutants reveal the importance of ΔpH-dependent photosynthesis-control in preventing light induced damage to both photosystem II and photosystem I - Roberto Barbato; Luca Tadini; Romina Cannata; Carlotta Peracchio; Nicolaj Jeran; Alessandro Alboresi; Tomas Morosinotto; Azfar Ali Bajwa; Virpi Paakkarinen; Marjaana Suorsa; Eva-Mari Aro; Paolo Pesaresi (Nature Research, 2022)
Although light is essential for photosynthesis, when in excess, it may damage the photosynthetic apparatus, leading to a phenomenon known as photoinhibition. Photoinhibition was thought as a light-induced damage to photosystem II; however, it is now clear that even photosystem I may become very vulnerable to light. One main characteristic of light induced damage to photosystem II (PSII) is the increased turnover of the reaction center protein, D1: when rate of degradation exceeds the rate of synthesis, loss of PSII activity is observed. With respect to photosystem I (PSI), an excess of electrons, instead of an excess of light, may be very dangerous. Plants possess a number of mechanisms able to prevent, or limit, such damages by safe thermal dissipation of light energy (non-photochemical quenching, NPQ), slowing-down of electron transfer through the intersystem transport chain (photosynthesis-control, PSC) in co-operation with the Proton Gradient Regulation (PGR) proteins, PGR5 and PGRL1, collectively called as short-term photoprotection mechanisms, and the redistribution of light between photosystems, called state transitions (responsible of fluorescence quenching at PSII, qT), is superimposed to these short term photoprotective mechanisms. In this manuscript we have generated a number of higher order mutants by crossing genotypes carrying defects in each of the short-term photoprotection mechanisms, with the final aim to obtain a direct comparison of their role and efficiency in photoprotection. We found that mutants carrying a defect in the ΔpH-dependent photosynthesis-control are characterized by photoinhibition of both photosystems, irrespectively of whether PSBS-dependent NPQ or state transitions defects were present or not in the same individual, demonstrating the primary role of PSC in photoprotection. Moreover, mutants with a limited capability to develop a strong PSBS-dependent NPQ, were characterized by a high turnover of the D1 protein and high values of Y(NO), which might reflect energy quenching processes occurring within the PSII reaction center.